PENERAPAN RESTORATIF JUSTICE DALAM KASUS KECELAKAAN LALU LINTAS YANG DILAKUKAN OLEH ANAK DI WILAYAH KOTA MATARAM - NANDA IVAN NATSIR; ABDUL HAMID; SYAMSUL HIDAYAT (Universitas Mahasaraswati K. Mataram, 2021)
The purpose of this study was to find out and analyze the application of Restorative Justice in cases of traffic accidents committed by children in the city of Mataram. This study uses the method This research uses an empirical approach. The application of Restorative Justice to children who violate the Traffic Law is carried out by the Mataram City Resort Police through a diversion process as mandated by Article 1 Paragraph (7) of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, namely a process outside of criminal justice through diversion. The legal force made between the parties in traffic crimes by minors is related to the discretionary authority possessed by the Police, so that the police are authorized to make decisions or choose various actions in resolving problems of law violations or criminal cases they handle, including traffic criminal cases. In addition, as a manifestation of diversion efforts as mandated by the Law on the Juvenile Criminal Justice System, which aims to achieve peace between victims and children, resolve child cases outside the judicial process, prevent children from being deprived of independence, encourage the community to participate and instill a sense of responsibility in children. . The obstacles faced in the application of Restorative Justice in cases of traffic accidents committed by children in the city of Mataram are the families of the victims who do not want to forgive the families of the perpetrators and the existence of negative views from the community, especially victims of law enforcement officers in the application of the concept of restorative justice. .